The substrate specificity, enantioselectivity and structure of the (R)‐selective amine : pyruvate transaminase from Nectria haematococca. (7th April 2014) - Sayer, Christopher; Martinez‐Torres, Ruben J.; Richter, Nina; Isupov, Michail N.; Hailes, Helen C.; Littlechild, Jennifer A.; Ward, John M.
<x xml:space="preserve">Abstract</x> During the last decade the use of transaminases for the production of pharmaceutical and fine chemical intermediates has attracted a great deal of attention. Transaminases are versatile biocatalysts for the efficient production of amine intermediates and many have (S)‐enantiospecificity. Transaminases with (R)‐specificity are needed to expand the applications of these enzymes in biocatalysis. In this work we have identified a fungal putative (R)‐specific transaminase from the Eurotiomycetes Nectria haematococca, cloned a synthetic version of this gene, demonstrated (R)‐selective deamination of several substrates including (R)‐α‐methylbenzylamine, as well as production of (R)‐amines, and determined its crystal structure. The crystal structures of the holoenzyme and the complex with an inhibitor gabaculine offer the first detailed insight into the structural basis for substrate specificity and enantioselectivity of the industrially important class of (R)‐selective amine : pyruvate transaminases. Database The atomic coordinates and structure factors for the Nectria TAm in holoenzyme and gabaculine‐bound forms have been deposited in the PDB as entries 4cmd and 4cmf respectively. Structured digital abstract TAm and TAmbind by x-ray crystallography (View interaction)